Marijuana business workers most common news source. (June 2017) - Block, Steven
This study explores newspaper coverage of marijuana legalization in Colorado during the first two months of implementation in 2014. The analysis of 202 news articles marijuana business workers and users account for 29 percent of sources used in articles. The most commonly discussed benefit of legalization is taxation revenue, while arguments against legalization are more diverse.